TRANSAKSI PIHAK HUBUNGAN ISTIMEWA DAN MANAJEMEN LABA PADA PENAWARAN SAHAM PERDANA - Reni Yendrawati; Sophia Anggarda Paramitha (Jurnal Keuangan dan Perbankan, 2014)
This study was conducted with the background that many companies did earning management through transactions with a related party in Initial Public Offering (IPO). This study aimed to examine the influence of related party transaction about earnings management in IPO. The population in this study was companies listed in Indonesia Stock Exchange. The sampling method used for this study was purposive sampling. This study used 38 samples from non-financial firms that conducted IPO’s in the Indonesia Stocked Exchange in 2009-2011.Paired Sample t-test was used to examine the significant earnings management which was represented by ROA. Multiple linear regression used RP Sales, RP Purchases, and RP Liabilities to the effect of earnings management. The result of this study showed that there was no a significant change between ROAt=-1 and ROAt=0  IPO period. The related party sales transaction did not have a significant effect of earnings management. However, this study indicated that the related party purchases transaction had a significant negative effect  and related party liabilities transaction had a significant positive effect on earnings management.